3D GROUNDWATER FLOW MODEL IN SEMARANG URBAN AREA, INDONESIA. - , Adnan, M.S , Hendrayana. H , Putra, D.P.E , Jinno, K ([Yogyakarta] : HAGI, 2008)
Due to rapid development of all sectors in Semarang urban area, degradations of water in term of quality and quantity has been identified. In this city, groundwater is, now, one of the vital resources as drinking water because surface water in quantity and quality has been deteriorated. Then, by understanding the groundwater flow condition in this area is very important related to the sustainable use of this water resource. One of the appropriate methods to solve this kind of problem is by using groundwater modeling. Groundwater modeling, however, even as approximations, is a useful investigation tool that groundwater hydrologists may use for a number of applications. Moreover, the research is initiated with the aim of characterizing the hydrogeological conditions, understanding and simulating groundwater flow patterns as well as groundwater flow directions, assessing groundwater balance, and understanding the hydraulic interaction between river and groundwater in the study area. The model result from this research will be expected to become a helpful tool to assess the impact of changes of the groundwater regime in the environment, to set up/optimize the network monitoring, and to set up groundwater protection for future sustainable groundwater usage.